2015
DOI: 10.1179/2047773215y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and multidrug resistance in uropathogenicEscherichia coli

Abstract: Context: Escherichia coli is known as causative agent of urinary tract infections (UTIs) tends to form microcolonies in mucosa lining of urinary bladder known as biofilm. These biofilms make the organism to resist the host immune response, more virulent and lead to the evolution of antibacterial drug resistance by enclosing them in an extracellular biochemical matrix. Aims: This study was done to know the association of various virulence factors and biofilm production in uropathogenic E. coli (UPEC) and antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
76
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 13 publications
12
76
1
2
Order By: Relevance
“…Our data also showed a robust association between nonbiofilm‐forming E. coli and phenotypic expression of MDR when isolates were evaluated after bacterial culture of the urine. This finding contrasts with available literature, which generally has shown associations between biofilm‐forming bacteria and MDR . In the aforementioned literature, the definitions of resistance are variable and bacteria other than E. coli are considered, thus making extrapolation to our current data problematic.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Our data also showed a robust association between nonbiofilm‐forming E. coli and phenotypic expression of MDR when isolates were evaluated after bacterial culture of the urine. This finding contrasts with available literature, which generally has shown associations between biofilm‐forming bacteria and MDR . In the aforementioned literature, the definitions of resistance are variable and bacteria other than E. coli are considered, thus making extrapolation to our current data problematic.…”
Section: Discussioncontrasting
confidence: 83%
“…A biofilm is a complex organizational structure of sessile bacteria and their associated extracellular matrix. Reports have suggested biofilm formation in up to 80% of all microbial infections in humans, and a recent case series in India reported that 13.5% of uropathogenic E. coli isolated from humans have biofilm‐forming capability . The biofilm provides protective benefits to the bacteria including nutrient sharing and antibiotic resistance, antibiotic tolerance, or both by various mechanisms that result in increased pathogenicity and higher likelihood of treatment failure .…”
Section: Introductionmentioning
confidence: 99%
“…The highest occurrence of ESBL was 100.0% amongst the strong biofilm producers. This high incidence of ESBL reported in this study could be an indication of creation of selective drug pressure because of commonly use of cephalosporin and other antibiotics in our region [21].…”
Section: Discussionsupporting
confidence: 53%
“…; Mittal et al . ). Hence there is an urgency to explore alternate therapeutic agents to combat the diseases originating especially due to E. coli biofilm formation.…”
Section: Introductionmentioning
confidence: 97%
“…AI help the bacterial cells in the biofilm to secrete virulence factors, modulate the host immune response and accrue genetic changes. Biofilm renders the penetration of conventional antibiotics hard and make the cells less susceptible to the antibiotics (Ito et al 2009;Mittal et al 2015). Hence there is an urgency to explore alternate therapeutic agents to combat the diseases originating especially due to E. coli biofilm formation.…”
Section: Introductionmentioning
confidence: 99%